PENDIDIKAN DALAM MASYARAKAT YANG BERUBAH (Peranan Pendidikan dalam Membentuk Insan Kamil) - Muhammad In'am Esha (El-QUDWAH, 2014)
Oleh Muhammad In’am Esha Dosen Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang Email: muhammadinamesha@gmail.com  Abstract This Article trys to identify education role in society changing to form insan kamil. Insan Kamil in this context understood by human being owning efficiency of either through spiritual, moral, intellectual, and also the professional. Education as important aspect in developing of human being hold responsible in attending human being which has qualification insan kamil. Education role becomes progressively crucial of along with society condition which being knocked over by a globalization that distinguishing for example very keen competition, free market appearance of values socialize and cultural, and also the society tendency which progressively materialistic.